Reconstruction of Legal Protection Regulations for Teachers Who Commit Acts of Violence in an Educational Environment Based on the Value of Dignified Justice - Kiki Handoko Sembiring; Teguh Prasetyo; Sri Endah Wahyuningsih (International Journal Reglement & Society (IJRS), 2023)
Since the promulgation of Act No. 14 of 2005, teachers are given the authority to sanction their students who violate norms, both religious norms, moral norms and school rules, whether written or not. However, teachers who provide sanctions in the form of violence are often faced with legal problems, because they are considered to have violated under the provisions of Article 54 of Act No. 35 of 2014 concerning Child Protection. Act No. 14 of 2005, precisely Article 39 has regulated Legal Protection for teachers, however the regulation only provides protection for teachers from acts of violence from other parties, explicitly teachers as victims not as perpetrators, so the teachers are often faced with law enforcement officers and even upfront of the court, as perpetrators of crimes in general. So teachers who commit violent acts intended to discipline their students often lose their glory and nobility. Which results in the teacher becoming indifferent to the development of the personality of his students. The glory and nobleness of the teacher as a lamp of character-forming life collapses when faced with law enforcement officers. Thus, the regulation of legal protection for teachers who commit acts of violence in the educational environment has not been based on the value of justice and dignity